Relação solo-vegetação em Floresta Atlântica de tabuleiro na Reserva Biológica de Sooretama - Machado, Luciana Ventura (2021)
The soil plays an important role in the heterogeneity of ecosystems, contributing to floristic differentiation, changes in species structure and diversity. The general objective of the present study was to analyze the attributes of the soil and its relationship with the vegetation in a remnant of Tableland Atlantic Forest, Sooretama Biological Reserve, Espírito Santo, Brazil. For that, this thesis was divided into five chapters. In chapter 1, from morphometric terrain attributes derived from Digital Elevation Model, an attempt was made to understand the environmental dynamics of the Sooretama Biological Reserve (SBR). In chapter 2, the study of the floristic composition and horizontal structure of the vegetation in stretches of the SBR was carried out by means of a phytosociological survey, in Rapeld modules (250 m x 40 m) distanced to 50 m, 250 m, 500 m and 750 m on the east side of the BR-101 highway, from the edge to the interior of the forest remnant. In chapter 3, the chemical and physical attributes of the soil were quantified at depths of 0-10 cm and 10-20 cm and evaluated their distribution patterns within a remnant of Tableland Atlantic Forest, SBR. In chapter 4, the biological attributes of the soil and soil organic matter compartments were quantified in winter and summer and their distribution patterns were evaluated within a remnant of Tableland Atlantic Forest, SBR. In chapter 5, the relationship between soil and vegetation was evaluated in stretches of a remnant of Tableland Atlantic Forest, SBR, adjacent to BR-101 federal highway. The SBR presented a predominance of the association of dystrocohesive yellow Argisol and dystrocohesive yellow Latosol, in flat to smooth wavy relief. The Alseis involuta, Brosimum guianense, Lecythis lurida, Manilkara longifolia, Rinorea bahiensis, Swartzia acutifolia and Virola gardneri were positively associated with soil resistance to root penetration, to the clay fraction; and negatively to the fine sand fraction and available P. In the winter, these species correlated positively with soil moisture and negatively with C stock; while in summer, these species correlated positively with N from the fulvic acid fraction and anaerobically mineralizable N; and negatively with soil temperature.